Laboratory and in-situ non-destructive methods to evaluate the thermal transmittance and behavior of walls, windows, and construction elements with innovative materials: A review - Soares, Nelson (2019)
The experimental characterization of the overall thermal transmittance of homogeneous, moderately- and non-homogeneous walls, windows, and construction elements with innovative materials is very important to predict their thermal performance. It is also important to evaluate if the standard calculation methods to estimate the U-value of new and existing walls can be applied to more complex configurations, since the correct estimation of this value is a critical requirement when performing building energy simulations or energy audit. This paper provides a survey on the main methods to measure the thermal transmittance and thermal behaviour of construction elements, considering laboratory conditions and in-situ non-destructive measurements. Five methods are described: the heat flow meter (HFM); the guarded hot plate (GHP); the hot box (HB), considering the guarded HB (GHB) and the calibrated HB (CHB); and the infrared thermography (IRT). Then, previous studies dedicated to the assessment of the thermal performance of different heavy- and light-weight walls are discussed. Particular attention is devoted to the measurement of the U-value of non-homogeneous walls, including the effect of thermal bridging caused by steel framing or mortar joints, and the presence of PCMs or new insulation materials in the configuration of the walls.